ONE-PIECE DENTAL IMPLANT UNTUK REHABILITASI RUANG KANINUS YANG SEMPIT - Fredy Mardiyantoro; Ariyati Retno Pratiwi (Odonto : Dental Journal, 2017)
Background: Tooth loss has serious functional, esthetic disabilities, and compromising the patients’ quality of life. Dental implant treatment has become increasingly common for the management tooth loss. Different clinical situations, such as narrow edentulous space, are often encountered in which modifications have to be considered in order to achieve successful rehabilitation. One piece dental implan provided a solution for rehabilitation of narrow edentulous space. The purpose of this paper is to report a rehabilitation management of narrow edentulous space. Case Management: A 22-year-old woman had an upper right canine #13 malposition so there was a narrow space between upper right lateral insisiv #12 and upper right first premolar #14. The spacing between upper right lateral insisivus #12 and upper right first premolar #14 was found to be about 5 mm. Radiograph was assessed for type of bone and for the presence of any pathology. A patient given an initial dental treatment such as scalling root planning and extraction of caninus #13. Following the clinical evaluation, the procedure and complication of implant therapy were explained and consent taken for proposed treatment. One piece dental implant site was anesthetized. Flaps on the buccal aspect were raised. One Piece dental implant inserted using dental implant kit. On completion of treatment, the patient’s esthetics and funcions improved. Conclusion: This study observed that one piece dental implants are suitable for rehabilitation of narrow edentulous space